Implementasi Reading Corner dalam Menumbuhkan Minat Membaca Peserta Didik Madrasah Ibtidaiyah - Susetiyo, Ari; Yuanita, Dianis Izzatul; Nisa, Rofiatun (IBTIDA', 2023)
This paper discusses the implementation of the reading corner in fostering interest in reading learners. This study was conducted at SDN Banjarmlati 2. In fourth-grade students, this study uses a type of qualitative descriptive research, then the data collection technique using observation and interviews, the subject of this study is the fourth-grade students. The data analysis technique uses triangulation. The results of this study showed that the reading corner doing and the implementation of the reading corner resulted in enthusiastic learners, and then the reading culture began to exist, with the reading corner learners becoming enterprising readers. It shows that it can establish interest in reading from learners. Then it can be concluded that the reading corner is very helpful to foster reading interest from learners. Furthermore, Reading Corner has supporting factors including support from homers, and teachers, and is also quite effective in filling student activities.